KOMUNIKASI PEMERINTAH DALAM PENGELOLAAN TAMBANG DI KABUPATEN GOWA - Herman K; Muhlis Madani; Muchlas M Tahir (Otoritas : Jurnal Ilmu Pemerintahan, 2015)
This study aims to determine the communication of government in managing quarry class C in District Pallangga. The method used in this study is a qualitative description of the approach. Data collection techniques in this research is observation, interview and documentation. The results showed that: the communication of government in the management of quarry class C deemed to be lacking, it is reflected: informative communication or communication that aims to provide information to others about the management of quarry class C is still lacking; Persuasive communication or communication that aims to change attitudes, opinions, or other people's behavior regarding the management of quarry class C is still lacking. Factors that inhibit the communication of government in the management of quarry class C consists of; coordination, government assertiveness, control, public attitudes and awareness of the mine owners. While supporting factor is the government communications and public disclosure. Penelitian ini bertujuan untuk mengetahui komunikasi pemerintah dalam mengelola tambang galian golongan C di Kecamatan Pallangga. Metode yang digunakan dalam penelitian ini adalah pendekatan deskripsi kualitatif.Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi.Hasil penelitian menunjukkan bahwa:komunikasi pemerintah dalam pengelolaan tambang galian golongan C dianggap masih kurang, hal ini tercermin dari: komunikasi informatif atau komunikasi yang bertujuan untuk memberikan informasi kepada orang lain tentang pengelolaan tambang galian golongan C masih kurang; Komunikasi persuasif atau komunikasi yang bertujuan untuk mengubah sikap, pendapat, atau perilaku orang lain tentang pengelolaan tambang galian golongan C masih kurang. Faktor-faktor yang menghambat komunikasi pemerintahan dalam pengelolaan tambang galian golongan C terdiri dari; koordinasi, ketegasan pemerintah, pengawasan, sikap masyarakat dan kesadaran pemilik tambang.Sedangkan faktor pendukungadalah komunikasi pemerintahan dan keterbukaan masyarakat.